Q: Multiply.
(8x4)(6x3)(-5x6)

A: This conversation has been flagged as incorrect. New answers have been added below ....

ArslanBasit|Points 1795|

emdroberts|Points 70|

Expert answered|bongche|Points 2555|

Question

Asked 7/7/2012 4:27:17 PM

Updated 6/8/2014 3:49:40 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [6/8/2014 3:48:47 PM]

Rating

3

(8x^4)(6x^3)(-5x^6) = -240x^13

Added 6/8/2014 3:48:01 PM

This answer has been confirmed as correct and helpful.

3

-9x^4(5x - 2) = -45x^5 + 18x^4

Added 6/8/2014 3:48:41 PM

This answer has been confirmed as correct and helpful.

3

(9m + 10)^2

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

= (9m + 10)(9m + 10)

= 81m^2 + 90m + 90m + 100

= 81m^2 + 180m + 100

Added 6/8/2014 3:49:40 PM

This answer has been confirmed as correct and helpful.

Multiply.
(x + 2)(x - 4)
x represents something **Weegy:** Sequence of development would be the order in which the development happens and the rate of development is the speed at which development happens. The difference is important because speed does not necessarily have to do with the sequence. **User:** I dont understand that. can you multiply this? **Weegy:** Your question is not displayed in my screen may i know what you dont understand? **User:** what is (x+2) Multiplied by (x-4) **Weegy:** x=-4 **User:** Multiply
(9m + 10)*2
**Weegy:** 38m **User:** Multiply.
-9x4*(5x - 2)
**Weegy:** If 5x - 3 **User:** Multiply
(8x4)*(6x3)*(-5x6)
**Weegy:** The answer is -12960 **User:** Simplify
(63a)3
**Weegy:** Can you kindly clarify your question please , is it Simplify. (63a) x 3 or , Simplify. (63a)^3 ? **User:** its times 3 **Weegy:** = 6 **User:** Evaluate.
(-9)*0
**Weegy:** The answer is 1. Anything to the power of 0 will equal 1. Try it on your calculator. **User:** Subtract.
(3x3 + 2x5 - 1 + 7x4) - (5 + 9x4 + 9x5 - 5x3)
**Weegy:** 11x5 + 16x4 - 2x3 ? 6 **User:** Add.
(-5 + 6x7 + 2x5) + (9x7 + 5x5 + 9)
**Weegy:** 5x5= 25 **User:** Evaluate the polynomial.
x2 + 3y2 + 2xy, when x = 4 and y = 2 **Weegy:** Please clarify your question (More)

Question

Expert Answered

Updated 4/27/2014 10:50:06 PM

9 Answers/Comments

(63a)*3 = 189a

Added 4/27/2014 10:43:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:09 PM]

(-9)*0 = 0

Added 4/27/2014 10:44:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:10 PM]

(3x^3 + 2x^5 - 1 + 7x^4) - (5 + 9x^4 + 9x^5 - 5x^3)

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

= 3x^3 + 2x^5 - 1 + 7x^4 - 5 - 9x^4 - 9x^5 + 5x^3

= 8x^3 - 2x^4 - 7x^5 - 6

Added 4/27/2014 10:45:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:46:11 PM]

(-5 + 6x^7 + 2x^5) + (9x^7 + 5x^5 + 9)

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

= -5 + 6x^7 + 2x^5 + 9x^7 + 5x^5 + 9

= 4 + 15x^7 + 7x^5

Added 4/27/2014 10:47:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/27/2014 10:48:45 PM]

27,010,316 questions answered

There are no comments.